EEG sensorimotor correlates of translating sounds into actions - Pineda, Jaime A.; Grichanik, Mark; Williams, Vanessa; Trieu, Michelle; Chang, Hailey; Keysers, Christian (Frontiers in Neuroscience, 2013)
Understanding the actions of others is a necessary foundational cornerstone for effective and affective social interactions. Such understanding may result from a mapping of observed actions as well as heard sounds onto one’s own motor representations of those events. To examine the electrophysiological basis of action-related sounds, EEG data were collected in two studies from adults who were exposed to auditory events in one of three categories: action (either hand- or mouth-based sounds), non-action (environmental sounds), and control sounds (scrambled versions of action sounds). In both studies, triplets of sounds of the same category were typically presented, although occasionally, to insure an attentive state, trials containing a sound from a different category were presented within the triplet and participants were asked to respond to this oddball event either covertly in one study or overtly in another. Additionally, participants in both studies were asked to mimic hand- and mouth-based motor actions associated with the sounds (motor task). Action sounds elicited larger EEG mu rhythm (8-13 Hz) suppression, relative to control sounds, primarily over left hemisphere, while non-action sounds showed larger mu suppression primarily over right hemisphere. Furthermore, hand-based sounds elicited greater mu suppression over the hand area in sensorimotor cortex compared to mouth-based sounds. These patterns of mu suppression across cortical regions to different categories of sounds and to effector-specific sounds suggest differential engagement of a mirroring system in the human brain when processing sounds.